Program-method for Storing Secret Information Using Vernam Cipher & AES - Kutsman, Vladyslav (European Journal of Applied Sciences, 2025)
Information security has been and will be one of the key positions both in business and in scientific work or for storing personal information. Reports, receipts, guarantees of information security of clients - all these are very important aspects that ensure the credibility of the company. But also very important is the safety of information during the work of the company itself or personal information of an individual or employee, for example, this can be an algorithm or program code that needs to be placed on github, but in such a form that only a few people can read it. Or certain financial statements of an accountant of a financial company, which should be seen only by the accountant himself and, at most, the owner. And in the case of a financial company, data leakage can be a reason for at least a loss of credibility, profit, or even the possibility of further business activity. This article presents software that implements an algorithm for storing file data on a permanent storage device of a computer using Vernam encryption and AES encryption, which can be used when working both in the workplace and in the private area of life, allowing you to conveniently and safely store information without fear of further data leakage. It is also very important that the proposed software does not require additional hardware elements in a computer or work laptop and, of course, can work with both local data and data from the network.